The Pusan International Film Festival 1996-2005: South Korean cinema in local, regional, and global context - Ahn, SooJeong (2008)
Despite the growing academic attention to film festivals, there has been little critical discourse about such events staged outside the West. This thesis aims to address this gap by providing a social, political and cultural exploration of the Pusan International Film Festival (PIFF) in South Korea between 1996 and 2005. The thesis utilises empirical research to reveal how the festival staked out a unique and influential position within a rapidly changing global landscape. Particular attention is paid to the organisersors' use of an Asian regionalisation strategy to promote the festival locally and globally. This study claims that PIFF has gone further than any other film festival in constructing a regional identity and maintaining a strong and mutually beneficial link to its national film industry. Research into PIFF's special relationship with both the national and regional film industries uncovers the previously unexplored roles that film festivals play in film production, in addition to their traditional functions of exhibition and distribution. To place this analysis in context, the thesis examines the politico-economic factors that influenced the establishment of the festival, its programming, the project market (the Pusan Promotion Plan), and its tenth anniversary in 2005. The study argues that analysis of PIFF reveals tensions and negotiations between the "national" and the "transnational" in the wake of economic and cultural globalisation in East Asia. The thesis serves as a case study of how contemporary film festivals adjust their roles and identities to adapt to local, regional and global change.